The Role Of Education Management In Improving Learning Innovation - seffiani dwi (Gestion Educativa, 2024)
Innovation in learning has become the main focus to improve the quality of education in many countries. With the development of information and communication technology and the changing needs of learners in the 21st century, schools are faced with the challenge of continuously adapting and developing effective and relevant learning methods. The role of education management is crucial in this context. Good management can create a supportive environment for innovation and encourage the implementation of new, more effective learning methods. Education management includes school leadership, teacher professional development, resource management and the establishment of a school culture that supports innovation. Visionary and supportive leadership can be a catalyst for positive change in schools, encouraging teaching staff to innovate in their teaching methods. Continuous professional development for teachers is also important, providing them with opportunities to continue learning and developing. Efficient and effective resource management supports learning innovation by ensuring adequate infrastructure, such as the latest educational technology and innovative teaching materials. Building a school culture that supports collaboration and experimentation is also important to create a conducive environment for innovation. This research aims to explore the role of education management in enhancing learning innovation in schools. Through a qualitative approach with case studies in several high schools implementing learning innovations, this research identifies key factors that encourage or hinder innovation. By understanding the role of education management, it is expected that effective strategies can be found to improve the quality of learning in various schools.